1985
DOI: 10.3758/bf03199271
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of pigeons to prereinforcer and postreinforcer delay

Abstract: Delay between choice and receipt of reinforcement (prereinforcer delay) and delay between receipt of reinforcement and the next opportunity to choose (postreinforcer delay) were varied in a discretetrials choice paradigm using four pigeons. The pigeons consistently chose the reinforcer with the smaller prereinforcer delay. Variations in postreinforcer delay did not affect choice unless prereinforcer delays were equal. The results support previous findings that prereinforcer delays contribute disproportionately… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
2

Year Published

1987
1987
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(38 citation statements)
references
References 17 publications
0
36
2
Order By: Relevance
“…8C). The idea that animals suboptimally incorporate postreward delays into their strategies is supported by other studies, as well (Lea, 1979;Logue et al, 1985;Smethells & Reilly, 2014;Stephens & Dunlap, 2009). …”
Section: The Problematic Postreward Buffermentioning
confidence: 74%
See 2 more Smart Citations
“…8C). The idea that animals suboptimally incorporate postreward delays into their strategies is supported by other studies, as well (Lea, 1979;Logue et al, 1985;Smethells & Reilly, 2014;Stephens & Dunlap, 2009). …”
Section: The Problematic Postreward Buffermentioning
confidence: 74%
“…As was noted above, Ainslie did consider the possibility, but reasoned that this was unlikely because of the large amount of training they received (Ainslie, 1975). Despite this, many studies have confirmed that even well-trained animals are either less attentive or completely inattentive to any delays occurring after the reward, as compared to delays occurring before it (Bateson & Kacelnik, 1996;Blanchard et al, 2013;Goldschmidt, Lattal, & Fantino, 1998;Green, Fisher, Perlow, & Sherman, 1981;Lea, 1979;Logue, Smith, & Rachlin, 1985;Mazur, 1987Mazur, , 1989Mazur & Logue, 1978;Mazur & Romano, 1992;Mazur, Snyderman, & Coe, 1985;Pearson et al, 2010;Snyderman, 1983; see also Gallistel & Gibbon 2000). These data suggest that animals do not fully consider the postreward delay in their choices, and thus it does not fulfill its purpose.…”
Section: The Problematic Postreward Buffermentioning
confidence: 99%
See 1 more Smart Citation
“…Note that reinforcement rate has been omitted from the right side of Equation 2, because many self-control experiments have used interdependent scheduling arrangements (Stubbs & Pliskoff, 1969) that equate exposure to both alternatives (e.g., Rodriguez & Logue, 1986). In addition, reinforcement rate has been shown to have virtually no effects on choice separate from delay for terminal links that deliver single reinforcers (Logue, Smith, & Rachlin, 1985;Mazur, Snyderman, & Coe, 1985). Two assumptions must be valid if the extended matching law is to provide an adequate account of self-control: (a) Delay and magnitude are independent dimensions of reinforcer value (Killeen, 1972), and (b) relative, not absolute, delays and magnitudes control preference.…”
mentioning
confidence: 99%
“…With this procedure, prebut not postreinforcer delays were fixed. However, previous research has found that subjects are relatively insensitive to variations in postreinforcer delays (see, e.g., Logue, Smith, & Rachlin, 1985).…”
Section: Methodsmentioning
confidence: 97%